Impact of fatty liver on hepatitis B virus replication and virologic response to tenofovir and entecavir - Ceylan, Bahadır; Arslan, Ferhat; Batırel, Ayşe; Fincancı, Muzaffer; Yardımcı, Cem; Fersan, Esra; Paşaoğlu, Esra; Yılmaz, Mesut; Mert, Ali (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: We aimed to evaluate the impact of non-alcoholic fatty liver disease (NAFLD) on viral kinetics and virologic response to tenofovir and entecavir treatment in patients with chronic hepatitis B virus (HBV) infection. Materials and Methods: This study was designed as a retrospective multicenter cohort study. The impact of hepatosteatosis on pre-treatment serum HBV DNA levels and also on the virologic response to either tenofovir or entecavir at 6 and 12 months of therapy was investigated. Results: A total of 145 cases were involved in the study [median age 40 (18–73) years, 90 (62%) males]. In multivariate analysis, it was detected that patients with NAFLD were older and had a higher body mass index (BMI) [Odds ratio (95% confidence interval) and p-value for age were 1.040 (1.003–1.079) and 0.033 and for BMI were 1.348 (1.190–1.528) and 0.0001, respectively]. When only the 43 patients who were younger than 35.5 years old and who had a BMI less than 27.59 were investigated, serum high-density lipoprotein (HDL) levels and serum HBV DNA levels were lower in patients with NAFLD in multivariate analysis [Odds ratio (95% confidence interval) and p-values for serum HDL level and HBV DNA level were 0.864 (0.061–0.980) and 0.023 and 0.995 (0.990–0.999) and 0.025, respectively]. Totally, 57 and 75 of the patients had received entecavir and tenofovir, respectively. Conclusion: Viral replication decreases in patients with chronic HBV infection in the presence of NAFLD, and NAFLD had no impact on the virologic response to entecavir and tenofovir treatment.